Economic Development and Its Implications for Religious Social Activities in Telang Karya Village, Muara Telang District, Banyuasin Regency - Eka Susanti Pratiwi (Medina-te : Jurnal Studi Islam, 2020)
The important objective of this research is to get an overview of economic development and its impact on religious activities in Telang Karya Village, Muara Telang District, Banyuasin Regency. The method used in this study is a qualitative method with a historiographical approach, from the aspects of sociology of religion and economics. The approach of this study was used to address issues related to economic development and its impact on people's religious activities. The data in this study were in the form of primary and secondary data. Primary data were obtained from interview, observation of the people who witnessed or experienced the events directly and documentation. In this study, the people who were interviewed and observed were the community and village officials. Meanwhile, village documents are the source of the data documented in this study. Next, secondary data is the supporting data obtained from the literature regarding the research title. Furthermore, the datawere interpreted by using frame theory of Sociology of Religion (Max Weber). The results obtained from this study showed that the influence of religion was in motivating its adherents to stabilize the economic conditions. Thus, the economic establishment is able to influence the level of enthusiasm of residents in Implementation of religious activities toward economic establishment. Another information got in this research was that there was an increasing amount of people who signed up to perform pilgrimage and worship Hajj also the incresed renovationof religious infrastructure.